- #1

- 1,800

- 53

Hi,

I'm told that a basic result in algebraic geometry is that all algebraic functions [itex]w(z)[/itex] of one variable given by the equation:

[tex]f(w,z)=a_n(z)w^n+a_{n-1}(z)w^{n-1}+\cdots+a_0(z)=0[/tex]

can be written in terms of fractional power series of the form:

[tex]w(z)=\sum_{n=-\infty}^{\infty}a_n \left(z^{1/d}\right)^n[/tex]

Might someone here suggest an accessible reference that goes over the proof or perhaps take a moment to explain some of the basic ideas behind the proof to me?

Thanks,

Jack

I'm told that a basic result in algebraic geometry is that all algebraic functions [itex]w(z)[/itex] of one variable given by the equation:

[tex]f(w,z)=a_n(z)w^n+a_{n-1}(z)w^{n-1}+\cdots+a_0(z)=0[/tex]

can be written in terms of fractional power series of the form:

[tex]w(z)=\sum_{n=-\infty}^{\infty}a_n \left(z^{1/d}\right)^n[/tex]

Might someone here suggest an accessible reference that goes over the proof or perhaps take a moment to explain some of the basic ideas behind the proof to me?

Thanks,

Jack

Last edited: